Attachment theory and research new directions and emerging themes - Simpson, Jeffry A.; Rholes, W. Steven (William Steven). (New York The Guilford Press, 2015)
"This volume showcases the latest theoretical and empirical work from some of the top scholars in attachment. Extending classic themes and describing important new applications, the book examines several ways in which attachment processes help explain how people think, feel, and behave in different situations and at different stages in the life cycle. Topics include the effects of early experiences on adult relationships; new developments in neuroscience and genetics; attachment orientations and parenting; connections between attachment and psychopathology, as well as health outcomes; and the relationship of attachment theory and processes to clinical interventions. Key Words/Subject Areas: attachment research, attachment security, attachment theory, couple interventions, developmental psychology, dyadic regulation process, emotion, parenting, psychopathology, relationships, romantic functioning, romantic attachment Audience: Researchers and students in social, developmental, personality, and clinical psychology. Serves as a primary or supplemental text in advanced undergraduate or graduate courses on attachment, close relationships, interpersonal processes, and family relationships "-- Provided by publisher.
Psychopathology and attchment Attachment theory in organizational settings / Ramona L. Paetzold -- Health and attachment processes Adult attachment style and parenting An attachment-theoretical perspective on optimal dependence in close relationships Attachment and aged care On the convergence of sexual urges and emotional bonds : the interplay of the sexual and attachment systems during relationship development Attachment and dyadic regulation processes Stress and attachment Attachment-related preventive interventions Fooled around and fell in love : the role of sex in adult romantic attachment formation The neuroscience of attachment : using new methods to answer old (and new) questions Attachment : a guide to a new era of couple interventions Early attachment experiences and romantic functioning : developmental pathways, emerging issues, and future directions Introduction : new directions and emerging themes in attachment theory and research Tsachi Ein-Dor and Guy Doron -- Susan M. Johnson, Marie-France Lafontaine, and Tracy L. Dalgleish Gery C. Karantzas and Jeffry A. Simpson -- Mary Dozier and Caroline K. P. Roben -- Paula R. Pietromonaco, Cassandra C. DeVito, Fiona Ge, and Jana Lembke -- Jason D. Jones, Jude Cassidy, and Phillip R. Shaver -- Brooke C. Feeney, Meredith Van Vleet, and Brittany K. Jakubiak -- Gurit E. Birnbaum -- Nickola C. Overall and Edward P. Lemay, Jr. -- Mario Mikulincer and Phillip R. Shaver -- Lisa M. Diamond -- Boosting attachment security in adulthood : the "broaden-and-build" effects of security-enhancing mental representations and interpersonal contexts Vivian Zayas, Sarah Merrill, and Cindy Hazan -- Omri Gillath -- R. Chris Fraley and Glenn I. Roisman -- W. Steven Rholes and Jeffry A. Simpson --
Keywords: Attachment behavior; Object attachment